Finnish-Enriched SLC26A7 Variant in Congenital Hypothyroidism: Clinical Spectrum, Thyroid Histopathology, and Expression Analysis - Niuro, Laura; Ojala, Johanna; Ravi, Rowmika; Melnyk, Vladyslav; Linnossuo, Veli; Palmu, Sofia; Jännäri, Meeri; Tyystjärvi, Sofia; Löf, Christoffer; Patyra, Konrad; Makkonen, Kristiina; Jääskeläinen, Jarmo; et al. (United States, 2026)
Background:
Defects in thyroid hormone synthesis at birth lead to congenital hypothyroidism (CH). Recently, pathogenic variants in the SLC26A7 gene have been linked to dyshormonogenetic goitrous CH. This anion transporter is highly expressed in the thyroid and is involved in thyroid hormone synthesis; however, its exact function and cellular localization remain unclear. In this study, we investigated SLC26A7 variants in Finnish patients with CH, characterized the phenotypes, and analyzed thyroid-specific gene expression.
Methods:
SLC26A7 variants were identified from a clinical CH cohort (n = 139) using exome sequencing, and the FinnGen database (R12 release) was screened for disease associations. Thyroid histology and thyroid-specific gene expression were analyzed in six human samples (including two homozygous SLC26A7 pathogenic variant carriers, patients with goitrous and hyperactive thyroids, and normal controls) and in thyroids from different mouse models (including hypo- and hyperthyroid mice, thyroid-specific G-protein deficient, and Slc26a7-knockout mice).
Results:
Four CH patients from four novel families carried the homozygous SLC26A7 (c.1893delT, p.F631Lfs*8) pathogenic variant. Two had large trachea-compressing goiters, requiring thyroidectomy already at birth. In addition, one homozygous participant with normal CH screening results developed hypothyroidism at age 16, and one patient with heterozygous SLC26A7 pathogenic variant had permanent CH at birth. Dentofacial abnormalities were frequently noted, including enamel hypoplasia (in four carriers), pro- or retrognathia, and malocclusion requiring orthodontic treatment (in 8/24 carriers). Thyrocyte hypertrophy with large colloid aggregates was a hallmark of homozygous patients. FinnGen screening revealed a 75-fold enrichment of the variant in the Finnish population, identifying a few other homozygous and seven heterozygous cases with early-onset hypothyroidism and dentofacial abnormalities. In human thyrocytes, SLC26A7 was localized to the basolateral membrane, with intense staining in hyperthyroid samples, while in mouse thyroid models, its expression pattern depended on dietary iodide levels, thyrotropin signaling, and GNAS activity.
Conclusions:
We describe variable phenotypes associated with the SLC26A7 pathogenic variant, ranging from severe CH with large congenital goiters to delayed onset hypothyroidism and dentofacial abnormalities. SLC26A7 shows thyrotropin-, GNAS-, and dietary iodine-dependent basolateral localization, suggesting their role in phenotypic variations.